The Possible Opportunities and Challenges of Using Drones in Last Mile Delivery - Tancharoenlarp, Thanrada (2019)
The increase of home delivery demand causes the last mile logistics becomes a crucial stage in order to moving goods from the warehouse to the customers. The idea of using drones or Unmanned Aerial Vehicles (UAVs) are receiving more attention from many researchers and logistics companies. According to drones can be operated without costly human pilot requirements, be able to fly directly to the destination without following the road networks which avoid road congestion and release less greenhouse gas emission level compared to other delivery vehicles. On the other hand, the challenges related to pressure and concern from people and public agency in several perspectives including regulations, safety and privacy issues. Plus, limitation capacity of the drones such as battery endurance, speed and flight range are another major of the drone itself. Apart from that, this study proposed the Capacitated Vehicle Routing Problem with drone (CVRPD) under payload constraint. To solve the problem, the mathematical formulation and OR-Tools are adopted. The findings highlighted that total delivery distance of all drones are approximately double-times higher than a traditional delivery vehicle that be able to load larger and heavier packages. These can be highlighted as drones does not suitable for all conditions of delivery, especially the customer nodes that far from each other. However, this study still leave some gap for the further studies to consider more related limitations and restrictions such as time-window constraint and flight range limitation.